Pharmacokinetic and Pharmacodynamic Impacts of Depot Medroxyprogesterone Acetate Use on HIV Pre-exposure Prophylaxis in Women. (1st October 2020) - Tarleton, Jessica; Chen, Beatrice A.; Meyn, Leslie A.; Hendrix, Craig W.; Marzinke, Mark A.; Achilles, Sharon L.
Abstract : Background: Depot medroxyprogesterone acetate (DMPA) is a commonly used contraceptive in areas where use of tenofovir disoproxil fumarate and emtricitabine for HIV pre-exposure prophylaxis (PrEP) is increasing. Objectives: We aimed to investigate the impact of DMPA on PrEP drug pharmacokinetics and pharmacodynamics in women using PrEP before and after DMPA administration. Methods: In this pilot study, 12 HIV-negative women ages 18–45 underwent biological sample collection at 3 time points: before study drug, after 2 weeks of daily PrEP use alone, and after 2 weeks of daily PrEP and concomitant DMPA use. We measured drug and drug metabolites in plasma, peripheral blood mononuclear cells, cervicovaginal fluid, cervical tissue, and rectal fluid after each 2-week course of PrEP. We measured HIV replication ex vivo in genital tissue biopsies and innate anti-HIV activity in cervicovaginal fluid before PrEP and after both courses. We compared drug concentrations after PrEP alone to after PrEP and DMPA in the same participant using Wilcoxon signed-rank tests. We used mixed effects linear regression models to compare pharmacodynamic measures for each participant at predrug baseline, after PrEP alone, and after PrEP and DMPA. Results: We found no significant differences in PrEP drug and drug metabolite concentrations in any compartment during concomitant DMPA use compared with use of PrEP alone, except for a reduction in emtricitabine concentration in cervical tissue. We found no difference in HIV replication in cervical tissue or anti-HIV activity in cervicovaginal fluid during concomitant DMPA and PrEP use compared with during PrEP use alone. Conclusions: Concomitant use of DMPA does not clinically alter pharmacokinetics or pharmacodynamics of PrEP in women. These data support the safety of DMPA use in women using PrEP. Abstract : Supplemental Digital Content is Available in the Text.